2022
DOI: 10.3390/nu14153083
|View full text |Cite
|
Sign up to set email alerts
|

Adequate Dietary Intake and Vitamin D Supplementation: A Study of Their Relative Importance in Determining Serum Vitamin D and Ferritin Concentrations during Pregnancy

Abstract: Vitamin D is essential for human health. However, it is not clear if vitamin D supplementation is necessary for all pregnant women. This study examines the relative importance of dietary patterns and vitamin D supplementation frequency in determining serum 25-hydroxyvitamin D (25(OH)D) and ferritin concentrations among pregnant women in Hong Kong, China. A total of 572 healthy women were recruited from antenatal clinics at 25–35 weeks pregnant. Participants completed an electronic version of the food frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Given that these nutrients are essential for fetal development, this is an issue of concern. Briefly, it is known that iron deficiency can lead to anemia, which can increase the risk of premature birth, low birth weight and other complications [ 39 , 40 ]; prenatal vitamin D deficiency has been linked to an increased risk of gestational diabetes, pre-eclampsia and premature birth [ 3 , 4 , 9 ], and can also affect calcium metabolism, leading to problems for bone health in both mother and child [ 41 ]; and finally, vitamin B9 insufficiency during pregnancy may results in preterm delivery, an increased risk of neural tube defects, and also impaired cognitive development in children [ 42 , 43 , 44 ]. However, inadequate intake and nutritional deficit of iron, vitamin D and vitamin B9 during pregnancy is not an isolated problem, but is widespread throughout Europe, as reported by current reviews [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that these nutrients are essential for fetal development, this is an issue of concern. Briefly, it is known that iron deficiency can lead to anemia, which can increase the risk of premature birth, low birth weight and other complications [ 39 , 40 ]; prenatal vitamin D deficiency has been linked to an increased risk of gestational diabetes, pre-eclampsia and premature birth [ 3 , 4 , 9 ], and can also affect calcium metabolism, leading to problems for bone health in both mother and child [ 41 ]; and finally, vitamin B9 insufficiency during pregnancy may results in preterm delivery, an increased risk of neural tube defects, and also impaired cognitive development in children [ 42 , 43 , 44 ]. However, inadequate intake and nutritional deficit of iron, vitamin D and vitamin B9 during pregnancy is not an isolated problem, but is widespread throughout Europe, as reported by current reviews [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal nutrition plays a crucial role in the proper development of pregnancy, maternal health, and the growth and development of the fetus [ 1 ]. Taking care of maternal dietary habits and optimal nutrient intake is of great importance to prevent nutritional imbalances, which can be detrimental to maternal and infant health and even lead to mid- and long-term consequences, such as low birth weight, fetal growth restriction and risk of chronic diseases later in life [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. It is, therefore, common to find guidelines recommending healthy eating behaviors during pregnancy to optimize maternal and fetal health [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an evidence-based study conducted by Michalski et al among Vietnamese women of reproductive age reported a positive association between serum, instead of dietary, vitamin D and Hb levels [26]. Additionally, Wong et al found that serum vitamin D levels were positively associated with serum ferritin levels in Chinese pregnant women [27]. However, the aforementioned studies did not explore any other iron-related biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary factors also contribute to vitamin D status during pregnancy [ 16 ]. However, few studies have addressed the relationship between Vitamin D and carbohydrate intake.…”
Section: Introductionmentioning
confidence: 99%